2004
DOI: 10.1016/j.jacc.2004.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of coronary magnetic resonance angiography as compared against conventional x-ray angiography

Abstract: In evaluable segments of the native coronary arteries, CMRA has moderately high sensitivity for detecting significant proximal stenoses and may have value for exclusion of significant multivessel CAD in selected subjects considered for diagnostic catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 56 publications
(18 reference statements)
1
35
0
1
Order By: Relevance
“…CMR angiography showed an 81% negative predictive value for excluding CAD in a multicenter controlled clinical trial, and meta-analyses 51,52 have shown diagnostic sensitivity and specificity ranging from 87% to 88% and 56% to 70%, respectively, which in general is lower than the diagnostic accuracy of CCTA.…”
Section: What Is the Diagnostic Accuracy Of Cmr Imaging?mentioning
confidence: 92%
“…CMR angiography showed an 81% negative predictive value for excluding CAD in a multicenter controlled clinical trial, and meta-analyses 51,52 have shown diagnostic sensitivity and specificity ranging from 87% to 88% and 56% to 70%, respectively, which in general is lower than the diagnostic accuracy of CCTA.…”
Section: What Is the Diagnostic Accuracy Of Cmr Imaging?mentioning
confidence: 92%
“…Furthermore, MRI does not expose the patient to ionizing radiation, thus, the usefulness of MRI has been investigated widely. However, the diagnostic accuracy of cardiac MRI in CAD varies widely according to the literature, with sensitivity ranging from 38% to 83%, and specificity ranging from 57% to 95% due to variable scanning protocols used in the studies [22]. Recent technical developments in MRI, especially with the emergence of 3.0 T MR imaging system have been shown to be a promising technique for performing cardiac MRI, with significant improvement of diagnostic value for detection of CAD [23,24].…”
Section: Disease; Diagnostic Value; Imaging Modalitiesmentioning
confidence: 99%
“…A meta-analysis of CAD diagnostic performance of coronary MRA [20] reports a moderately high sensitivity for detecting proximal stenoses but notes that distal segments can not be evaluated. The clinical study conducted in [21] on congenital heart disease diagnostic based on SSFP MR Imaging focuses therefore on proximal segments.…”
Section: Mography (Mdct) Electron Beam Computed Tomography (Ebct) Andmentioning
confidence: 99%